Design of Controller for Laser Semi-Active Proportional Navigation Device Based on LQG/LTR - Zhao, Jun; Wang, Changyu; Ai, Tiezhu; Huang, Yanfei; Zhao, Gang (2021 IEEE/ACIS 20th International Fall Conference on Computer and Information Science (ICIS Fall), 2021)
Aiming at the demand of improving anti-interference and real-time performance of a new type laser semiactive four-quadrant proportional guidance device, this paper proposes a controller architecture based on ARM+FPGA which improves the real-time performance and complex code pattern detection ability of the system by increasing the co-processing ability, and adopts LQG/LTR algorithm to design the control strategy of the servo tracking system to improve the fast and stable tracking ability and robustness. The experimental results show that the pulse acquisition accuracy of the system reaches 30ns, the analog acquisition synchronization accuracy reaches 13ns, the analog acquisition accuracy reaches 0.3%, the gain control response time is less than 3.77 ms, and the pseudorandom code recognition delay is less than 100ms, which effectively improves the real-time performance and robustness of the laser semi-active proportional guidance device.